Characterization of a pathogen induced thaumatin-like protein gene AdTLP from Arachis diogoi, a wild peanut. - Naveen Kumar Singh (Public Library of Science (PLoS), 2013)
Peanut (Arachis hypogaea L) is one of the widely cultivated and leading oilseed crops of the world and its yields are greatly affected by various biotic and abiotic stresses. Arachis diogoi, a wild relative of peanut, is an important source of genes for resistance against various stresses that affect peanut. In our previous study a thaumatin-like protein gene was found to be upregulated in a differential expression reverse transcription PCR (DDRT-PCR) study using the conidial spray of the late leaf spot pathogen, Phaeoisariopsis personata. In the present study, the corresponding full length cDNA was cloned using RACE-PCR and has been designated as AdTLP. It carried an open reading frame of 726 bp potentially capable of encoding a polypeptide of 241 amino acids with 16 conserved cysteine residues. The semi-quantitative RT-PCR analysis showed that the transcript level of AdTLP increased upon treatment with the late leaf spot pathogen of peanut, P. personata and various hormone treatments indicating its involvement in both, biotic and abiotic stresses. The antifungal activity of the purified recombinant protein was checked against different fungal pathogens, which showed enhanced anti-fungal activity compared to many other reported TLP proteins. The recombinant AdTLP-GFP fusion protein was found to be predominantly localized to extracellular spaces. Transgenic tobacco plants ectopically expressing AdTLP showed enhanced resistance to fungal pathogen, Rhizoctonia solani. The seedling assays showed enhanced tolerance of AdTLP transgenic plants against salt and oxidative stress. The transcript analysis of various defense related genes highlighted constitutively higher level expression of PR1a, PI-I and PI-II genes in transgenic plants. These results suggest that the AdTLP is a good candidate gene for enhancing stress resistance in crop plants.